Effects of Li2O and Na2O on the Crystallization Behavior of Lime-Alumina-Based Mold Flux for Casting High-Al Steels - Lu, Boxun; Chen, Kun; Wang, Wanlin; Jiang, Binbin (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2014)
With the development of advanced high strength steel (AHSS), a large amount of aluminum was added into steels. The reaction between aluminum in the molten steel and silica based mold flux in the continuous-casting process would tend to cause a series of problems and influence the quality of slabs. To solve the above problems caused by the slag–steel reaction, nonreactive lime-alumina-based mold flux system has been proposed. In this article, the effect of Li 2 O and Na 2 O on the crystallization behavior of the lime-alumina-silica-based mold flux has been studied by using the single hot thermocouple technology (SHTT) and double hot thermocouple technology (DHTT). The results indicated that Li 2 O and Na 2 O in the above mold flux system play different roles as they behaved in traditional lime-silica based mold flux, which would tend to inhibit general mold flux crystallization by lowering the initial crystallization temperature and increasing incubation time, especially in the high-temperature region. However, when their content exceeds a critical value, the crystallization process of mold fluxes in low temperature zone would be greatly accelerated by the new phase formation of LiAlO 2 and Na x Al y Si z O 4 crystals, respectively. The crystalline phases precipitated in all samples during the experiments are discussed in the article.